Major congenital malformations and residential proximity to a regional industrial park including a national toxic waste site: An ecological study - Polyakov Marina; Bilenko Natasha; Belmaker Ilana; Hershkovitz Reli; Kordysh Ella; Bentov Yaakov; Sarov Batia (BMC, 2006)
Abstract Background Public concern about exposure to emissions from the regional industrial park (IP), including 17 chemical plants and the national industrial toxic waste site, initiated this study of the possible association between major congenital malformations (MCM) and residence near the IP in Israel's Southern District. Methods The study was conducted during the period 1995-2000 and included 63,850 deliveries. Data on deliveries and MCM detected at births were obtained from the regional medical center, and stratified by ethnicity and type of locality. As exposure indicator we used distance categories (proximal and distant) and predominant wind direction from the IP. Distance stratification was based on the geographical distribution of the localities and complaints about the odor related to IP emissions. Based on these complaints, localities up to 20 km from the IP were considered proximal to the IP. Results Average rates of MCM were 5.0% and 4.1% for Bedouin and Jewish newborns, respectively. The rate of MCM for Bedouin from proximal localities was significantly greater compared with distant localities (5.6% vs. 4.8%; RR = 1.17 with 95% CI: 1.04-1.29). In the proximal Bedouin permanent localities, the MCM rate reached 8.2 %, which was significantly higher than in distant areas (RR = 1.63, 95% CI: 1.39-1.80). Significant risk increase of central nervous system MCM was found in these localities, compared to distant ones (RR = 2.27, 95% CI: 1.44-3.60). Among newborns from the traditional tribal settlements, proximity to the IP was associated with increased rates of the following MCM: 1) all combined, 2) those associated with chromosomal abnormalities, and 3) those defined as "others unclassified MCM." Comparison of autosomal recessive disease rates by proximity to the IP in Bedouin newborns indicates that the observed increased risk of MCM is not explained by consanguineous marriages. The rates of MCM in the Jewish population were similar among "exposed" and "unexposed" inhabitants. Conclusion Residential proximity to the IP is associated with increased rates of MCM among Arab-Beduin but not in Jewish populations. These observations indicate the need for public health protection of a vulnerable society in transition, although the relative importance of chemical exposure and health care utilization requires further study.